Targeting immuno-oncology metabolism for precision cancer therapy - Pajai, Sakshi; John, Jyoti E.; Tripathi, Satyendra Chandra (Frontiers in Oncology, 2023)
Immune cells play an important role in host defence against infection and cancer. In contrast to infection. cancer is a multidimensional disease where cancer cells require continuous activation of certain pathways to sustain their growth and survival. The tumor milieu plays an important role in defining the metabolic reprogramming to support this growth and evasion from the immune system. Cancer and stromal cells modulate each other’s metabolism during cancer progression or regression. The mechanism related to change in the metabolism and its role in the crosstalk between tumor and immune cells is still an area of immense importance. Targeting the immuno-oncology metabolism has immense potential to complement current treatment modalities and improve patient prognosis. This emerging aspect of immune-oncology metabolism is reviewed here, discussing therapeutic possibilities with different metabolic pathways and their impact on immune-oncology metabolism.